Giant Robber Crabs Monitored from Space: GPS-Based Telemetric Studies on Christmas Island (Indian Ocean) - Krieger, Jakob; Grandy, Ronald; Drew, Michelle M.; Erland, Susanne; Stensmyr, Marcus C.; Harzsch, Steffen; Hansson, Bill S. (PLOS ONE, 2012)
We investigated the navigational capabilities of the world's largest land-living arthropod, the giant robber crab Birgus latro (Anomura, Coenobitidae); this crab reaches 4 kg in weight and can reach an age of up to 60 years. Populations are distributed over small Indo-Pacific islands of the tropics, including Christmas Island (Indian Ocean). Although this species has served as a crustacean model to explore anatomical, physiological, and ecological aspects of terrestrial adaptations, few behavioral analyses of it exist. We used a GPS-based telemetric system to analyze movements of freely roaming robber crabs, the first large-scale study of any arthropod using GPS technology to monitor behavior. Although female robber crabs are known to migrate to the coast for breeding, no such observations have been recorded for male animals. In total, we equipped 55 male robber crabs with GPS tags, successfully recording more than 1,500 crab days of activity, and followed some individual animals for as long as three months. Besides site fidelity with short-distance excursions, our data reveal long-distance movements (several kilometers) between the coast and the inland rainforest. These movements are likely related to mating, saltwater drinking and foraging. The tracking patterns indicate that crabs form route memories. Furthermore, translocation experiments show that robber crabs are capable of homing over large distances. We discuss if the search behavior induced in these experiments suggests path integration as another important navigation strategy.